Pedoman Wanita Karir Dalam Islam : Telaah Pemikiran Muhammad bin Shalih Al Utsaimin - Abu Dzar Al Ghifari Marwan (Khulasah : Islamic Studies Journal, 2026)
Career women are one of the hotly discussed issues both for and against it, the discussion cannot be separated from the issue of rights and obligations for women, as well as Islam's view of the issue. This article discusses the guidelines for women in their careers from an Islamic perspective in the perspective of Muhammad bin Shalih Al Uthaymeen, in which he provides specifications for the ideal woman in Islam, as well as the guidelines that Islam provides in order to maintain the ideals of women in their careers. This study uses a qualitative method with a literature study approach (library research), which concludes that women will be allowed to have a career by paying attention to the guidelines provided by Islam.